Biodiversity and human livelihoods in protected areas : case studies from the Malay Archipelago - Sodhi, Navjot S.; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
This book was published in 2007. Protected areas have emerged as major arenas of dispute concerning both indigenous and environmental protection. In the Malay Archipelago, which contains two of the twenty-five biodiversity hotspots identified globally, rampant commercial exploitation is jeopardizing species and rural livelihoods. While protected areas remain the only hope for the imperiled biota of the Malay Archipelago, this protection requires consideration of the sustenance needs and economic aspirations of the local people. Putting forward the views of all the stakeholders of protected areas - conservation practitioners and planners, local community members, NGO activists, government administrators, biologists, lawyers, policy and management analysts and anthropologists - this book fills a niche in the area of biodiversity, and is a highly valuable and original reference book for graduate students, scientists and managers, as well as government officials and transnational NGOs.
Part I Conservation needs and priorities 7 -- 3 Delineating Key Biodiversity Areas as targets for protecting areas / Thomas M. Brooks, Naamal De Silva, Melizar V. Duya, Matt Foster, David Knox, Penny Langhammer, William Marthy R., Blas Tabaranza, Jr. 20 -- 4 A Master Plan for Wildlife in Sarawak: preparation, implementation and implications for conservation / Melvin T. Gumal, Elizabeth L. Bennett, John G. Robinson, Oswald Braken Tisen 36 -- 5 Indonesia's protected areas need more protection: suggestions from island examples / David Bickford, Jatna Supriatna, Noviar Andayani, Djoko Iskandar, Ben J. Evans, Rafe M. Brown, Ted Townsend, Umilaela, Deidy Azhari, Jimmy A. McGuire 53 -- 6 Birds, local people and protected areas in Sulawesi, Indonesia / Tien Ming Lee, Navjot S. Sodhi, Dewi M. Prawiradilaga 78 -- 7 Importance of protected areas for butterfly conservation in a tropical urban landscape / Lian Pin Koh 95 -- 8 Biodiversity conservation and indigenous peoples in Indonesia: the Krui people in southern Sumatra as a case study / Ahmad Kusworo, Robert J. Lee 111 -- 9 Involving resource users in the regulation of access to resources for the protection of ecosystem services provided by protected areas in Indonesia / Abdul Halim, Tri Soekirman, Widodo Ramono 122 -- Part II Conservation with and against people(s) 141 -- 12 Collaboration, conservation, and community: a conversation between Suraya Afiff and Celia Lowe / Suraya Afiff, Celia Lowe 153 -- 13 Hands off, hands on: communities and the management of national parks in Indonesia / Moira Moeliono 165 -- 14 Conservation and conflict in Komodo National Park / Ruddy Gustave, Henning Borchers 187 -- 15 Another way to live: developing a programme for local people around Tanjung Puting National Park, Central Kalimantan / Semiarto Aji Purwanto 203 -- 16 For the people or for the trees? A case study of violence and conservation in Ruteng Nature Recreation Park / Maribeth Erb, Yosep Jelahut 222 -- 17 Seas of discontent: conflicting knowledge paradigms within Indonesia's marine environmental arena / Chris Majors 241 -- 18 Strategy and subjectivity in co-management of the Lore Lindu National Park (Central Sulawesi, Indonesia) / Greg Acciaioli 266 -- 19 Indigenous peoples and parks in Malaysia: issues and questions / Hood Salleh, Keith A. Bettinger 289 -- 20 Protecting Chek Jawa: the politics of conservation and memory at the edge of a nation / Daniel P.S. Goh 311 -- 21 Integrating conservation and community participation in protected-area development in Brunei Darussalam / Azman Ahmad 330 -- Part III Legal and governance frameworks for conservation 347 -- 23 Introduction to Part III / Alan Khee-Jin Tan 349 -- 24 Protected-area management in Indonesia and Malaysia: the challenge of divided competences between centre and periphery / Alan Khee-Jin Tan 353 -- 25 Protecting sovereignty versus protecting parks: Malaysia's federal system and incentives against the creation of a truly national park system / Keith A. Bettinger 384 -- 26 What protects the protected areas? Decentralization in Indonesia, the challenges facing its terrestrial and marine national parks and the rise of regional protected areas / Jason M. Patlis 405 -- 27 Learning from King Canute: policy approaches to biodiversity conservation, lessons from the Leuser Ecosystem / John F. McCarthy, Zahari Zen 429.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Biodiversity conservation -- Malay Archipelago -- Case studies; Biodiversity conservation -- Economic aspects -- Malay Archipelago -- Case studies; Biodiversity conservation -- Government policy -- Malay Archipelago -- Case studies; Protected areas -- Malay Archipelago -- Case studies; Protected areas -- Economic aspects -- Malay Archipelago -- Case studies; Protected areas -- Government policy -- Malay Archipelago -- Case studies; Electronic books